1978
DOI: 10.1021/j100511a006
|View full text |Cite
|
Sign up to set email alerts
|

Positronium formation process in organic liquids

Abstract: The formation of positronium in benzene solutions containing a variety of halogenated compounds, such as CC14, CH2C12, C2HC13, 1,1,1-C2H3C13, o-C6H4CH3Br, o-C6H4Cl2, o-C6H4CH3C1, C6H5C1, and other mono-and dihalobenzene, was studied in the presence and absence of C6F6 additives. The observed /2 values, which are indicative of the number of thermalized positronium atoms formed, showed in each system a good correlation with dissociative electron attachment parameters of the solute species. C8F8 additives increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…I, the o-Ps formation fraction decreases as the Gd concentration increases, whereas the lifetime is almost constant. It can be noted that when a very small fraction of doper is added (0.01%) the formation fraction increases slightly with respect to the case of pure LAB: this is a known effect as explained in Ref [15]. The trends of the o-Ps lifetime and formation fraction as a function of the doper concentration are shown in Fig.…”
Section: A Lab+gdmentioning
confidence: 57%
See 1 more Smart Citation
“…I, the o-Ps formation fraction decreases as the Gd concentration increases, whereas the lifetime is almost constant. It can be noted that when a very small fraction of doper is added (0.01%) the formation fraction increases slightly with respect to the case of pure LAB: this is a known effect as explained in Ref [15]. The trends of the o-Ps lifetime and formation fraction as a function of the doper concentration are shown in Fig.…”
Section: A Lab+gdmentioning
confidence: 57%
“…It can be noted that when a very small fraction of doper is added (0.01%) the formation fraction increases slightly with respect to the case of pure LAB: this is a known effect as explained in Ref. [17].…”
Section: Concentration [%]mentioning
confidence: 65%
“…Over the years, abundant studies on free volume have been reported in molecular media like liquids, , polymers, ,, polymer blends, composites, , and to some extent in fibers , using positronium annihilation lifetime spectroscopy (PALS). Such studies include reports on free volume changes with the change in topology of polymers due to crystallinity, solvent casting, solvent evaporation rate, tensile stretching, and electric field effects .…”
Section: Introductionmentioning
confidence: 99%
“…Since the polymer chain orientation is closely associated with free volume, 26,27 the spatial distribution of molecular chains within the nanofiber needs further understanding in terms of associated free volume and its distribution. 26,28 Over the years, abundant studies on free volume have been reported in molecular media like liquids, 29,30 polymers, 27,28,31−34 polymer blends, 35−37 composites, 38,39 and to some extent in fibers 40,41 using positronium annihilation lifetime spectroscopy (PALS). Such studies include reports on free volume changes with the change in topology of polymers due to crystallinity, 28 solvent casting, 31 solvent evaporation rate, 42 tensile stretching, 27 and electric field effects.…”
Section: Introductionmentioning
confidence: 99%
“…The e †ect of various additives on Ps formation has been extensively studied for molecular liquids.4,12h19 One of the most important Ðndings is that the addition of an electron acceptor, such as nitrobenzene derivatives and chlorinated hydrocarbons, causes a marked reduction in the Ps intensity (inhibition of Ps formation).13h16 Interestingly, certain electron acceptors such as hexaÑuorobenzene were found (C 6 F 6 ) to increase the Ps yield (enhancement of Ps formation).17 Addition of these compounds to a solution containing a Ps inhibitor was found to recover the Ps yield reduced by the inhibitor (anti-inhibition of Ps formation).18,19 These phenomena of inhibition, enhancement and anti-inhibition of Ps formation have been successfully explained on the basis of the spur reaction model, although an attempt was made to interpret them with the help of the Ore model and reactions of hot Ps atoms. 13 Recently, we observed that the o-Ps yield in amorphous polymers was considerably reduced by addition of a nitrocompound, 2,2@-dinitrobiphenyl (DNB). 20…”
Section: Introductionmentioning
confidence: 99%